Analysis of the Implementation of Islamic Religious Education Learning in Elementary Schools - Ermawati; Faizah (Journal of Indonesian Primary School, 2025)
This article aims to reveal the concept of learning Islamic religious education in elementary schools. In its development, elementary school-age children have their own characteristics, where their thinking skills develop gradually. This needs to be understood wisely in order to deliver the success of educational goals. This research uses a descriptive qualitative approach with the library research method. The results of the study show that Islamic religious education in elementary schools has its own uniqueness. If in the past children's thinking power was still imaginative and egocentric, then in this period their thinking power has developed towards concrete, rational, and objective thinking. The scope of Islamic religious education studies includes the Qur'an, faith, morals, fiqh/worship, and Islamic cultural history. Educational methods that can be applied refer to the Quranic method, such as the amtsal method, the qishah method, the ibrah mauidzah method, the hiwar jadali method, the uswah hasanah method, and the targhib tarhib method. In addition, Islamic religious education can be carried out verbally or nonverbal, written or non-written, which aims to measure the intellectual, social, and spiritual competence of students. Thus, Islamic religious education is expected to be able to produce human beings who always strive to perfect faith, piety, and morals, and actively build Islamic civilization.